2013
DOI: 10.3354/aei00061
|View full text |Cite
|
Sign up to set email alerts
|

Turnover and fractionation of nitrogen stable isotope in tissues of grass carp Ctenopharyngodon idellus

Abstract: Determination of the isotopic turnover rate in the various tissues of an organism is one of the essential prerequisites for tracing the food sources of consumers and for elucidating trophic interactions in ecological studies using stable isotope analysis (SIA). Isotopic turnover and fractionation in the commercially important freshwater teleost grass carp Ctenopharyngodon idellus, however, are poorly understood so far. In the present study, we conducted a diet-switch experiment of C. idellus for 3 mo to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 50 publications
(28 reference statements)
2
25
0
Order By: Relevance
“…Other studies have, however, revealed that considerable differences in turnover rates can be apparent between fish tissues (Buchheister & Latour, 2010;Xia et al, 2013b), although their differences are often only minor (Hesslein et al, 1993;Sweeting et al, 2005;McIntyre & Flecker, 2006). Thus, tissue turnover differentiation, as well as the relative ordering of turnover rates among tissues, appears to be speciesspecific.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Other studies have, however, revealed that considerable differences in turnover rates can be apparent between fish tissues (Buchheister & Latour, 2010;Xia et al, 2013b), although their differences are often only minor (Hesslein et al, 1993;Sweeting et al, 2005;McIntyre & Flecker, 2006). Thus, tissue turnover differentiation, as well as the relative ordering of turnover rates among tissues, appears to be speciesspecific.…”
Section: Discussionmentioning
confidence: 88%
“…Buchheister and Latour (2010) studied summer flounder Paralichthys dentatus (Linnaeus, 1766) liver, blood and muscle tissue and found muscle had the slowest half-life (85 days). For grass carp Ctenopharyngodon idellus (Valenciennes, 1844), the estimated 15 N half-life of muscle was 68 days (Xia et al, 2013b). Where differences between tissue turnover rates are detected in fishes, they generally follow the pattern that more metabolically active tissues show faster stable isotope turnover rates (Tieszen et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resale or republication not permitted without written consent of the publisher carried out, especially for unstudied species (Fisk et al 2009, Xia et al 2013b.…”
Section: Abstract: Carbon Stable Isotope Turnover · Growth · Metabolmentioning
confidence: 99%
“…Its production has increased rapidly over recent decades (Xia et al 2013a(Xia et al , 2013b. However, the high stocking density with an artificial supply of formulated feed has resulted in a large amount of effluents.…”
Section: Introductionmentioning
confidence: 99%